Clinical usefulness of image‐enhanced endoscopy for the diagnosis of ulcerative colitis‐associated neoplasia - Kaoru Takabayashi; Motohiko Kato; Takanori Kanai (DEN Open)
Abstract Patients with a long history of ulcerative colitis (UC) are at risk of developing a significant complication known as UC‐associated neoplasia (UCAN). To reduce the risk of UCAN and the associated mortality, the current guidelines recommend initiating surveillance colonoscopy 8–10 years after confirmation of UC diagnosis. In recent years, advancements in endoscopic diagnostic technologies, including magnifying and image‐enhancing techniques, have allowed for the production of high‐contrast images that emphasize mucosal structures, vascular patterns, and color tones. Recently, image‐enhanced endoscopy technologies have become available and offer the potential to improve the qualitative endoscopic assessment of UCAN. The use of high‐definition chromoendoscopy enables the evaluation of subtle mucosal patterns in the colon. Magnifying narrow‐band imaging facilitates the visualization of mucosal vascular structures. Texture and color enhancement imaging processes structure, color tone, and brightness aspects more appropriately, whereas linked color imaging optimizes the emphasis on mucosal and vascular redness. Both techniques are expected to excel in the depiction of subtle color variations and mucosal changes characteristic of UCAN. This article provides an overview of the current status and future challenges regarding the use of various image‐enhanced endoscopy techniques in the diagnosis of UCAN.